GAGASAN PEMBERIAN HAK PISTOLE TERHADAP NARAPIDANA LANJUT USIA YANG DIJATUHI PIDANA PENJARA - Amirah, Kamilia; Erdiansyah, Erdiansyah; Andrikasmi, Sukamarriko (LPPM, Universitas Muhammadiyah Riau, 2025)
The large number of elderly people and predicted to increase every year has led Indonesia to an era ofaging population structure. This has an impact on the increase in the number of elderly prison inmates.The problem of overcapacity which is also in line with the problem of overbudgeting ultimately disrupts thefulfillment of their rights as vulnerable groups in correctional institutions. In fact, the only right that istaken away from prison inmates is freedom, so their other basic rights must still be respected. This type ofresearch can be classified into the type of normative legal research using data sources in the form ofsecondary data with data collection techniques using the literature review method. Then, the data isanalyzed and processed qualitatively, and produces descriptive data to then be concluded deductively.From the research results, there are two main things that can be concluded, first, there are four urgenciesof the idea, such are the increase in the number of elderly people has implications for the increase in thenumber of elderly prison inmates, the elderly as a vulnerable group guaranteed by law, changes in theconcept of prisons that seek to change criminal law to be more humanist by prioritizing humane treatmentof prison inmates, and the problem of prioritizing humane treatment of prisoners as an effort to makecriminal law more humanist. Second, the ideal idea of giving pistole rights to elderly prison inmates.